PENGARUH AKUNTANSI SEKTOR PUBLIK TERHADAP KINERJA ORGANISASI PUBLIK PADA RUMAH SAKIT UMUM DAERAH SYEKH YUSUF KABUPATEN GOWA - Ibrahim Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of this research is to know the effect of public sector accounting on the performance of public organization at the General Hospital of Sheikh Yusuf Area in Gowa Regency. While the method of analysis used in this study is a simple linear regression to test H. used to determine the effect of an event independent variable to an event of one dependent variable. The results of this study is public sector accounting has a significant effect on the performance of public organizations. Positive and significant influences with low categories indicate that public sector accounting has not played an important role in the performance of public organizations.